Two thousand years of Landscape—Human interactions at a coastal peninsula in Norway revealed through pollen analysis, shoreline reconstruction, and radiocarbon dates from archaeological sites - Hjelle, Kari Loe; Overland, Anette; Gran, Magnar Mojaren; Romundset, Anders; Ystgaard, Ingrid (Frontiers in Ecology and Evolution, 2022)
Human impact on long-term vegetation and biodiversity changes is often discussed on a general level, connecting palynological data to archaeological time periods. In the present paper we present environmental change during the last 2400 years on a coastal peninsula in Norway using pollen data from three sites: one lake and two bogs, in addition to 621 radiocarbon dates and in-context pollen samples from archaeological sites. Locally, a close relationship between palynological richness reflecting high landscape, habitat and floristic diversity, and the summed probability distribution of radiocarbon dates was found. During the settlement period 400 BCE–550 CE, concordant with maximum number of dates from archaeological contexts, a mosaic landscape containing infields and outfields developed. Cereals were cultivated and animals were grazing in heathlands that could provide both summer grazing and winter fodder. Additionally, seashores and wetlands were used for grazing. Settlement recession from 350 CE and abandonment following the 536 CE climate event, resulted in vegetation successions towards reforestation, abandonment of arable fields, and marshes turning into ombrotrophic peat. At the same time the distance to the sea, and to species rich shoreline meadows, continued to increase due to continuous postglacial land uplift in a flat landscape. A new increase in the summed probability distribution 900–1250 CE, is reflected in expansion of outfield pastures, heathlands in particular, a management that continued up into modern time. The local development is supported by the results on a regional scale, indicating overall climatic and social causes for observed vegetation changes. Both palynological richness and pollen-based landcover reconstructions indicate reforestation and less habitat diversity in the 6th century. On a regional scale, reforestation in the 15th century following the late medieval crises, is more pronounced than on the local scale, although both reflect increased exploitation of outfield resources.